The olfactory bulb endocast as a proxy for mammalian olfaction - Quentin Martinez; Cécile Molinier; Ilse K. Barraza-Soltero; Elena Berger; Kévin Le Verger; Anne-Claire Fabre; Guillaume Billet; Vincent Fernandez; Gabriel S. Ferreira; Thomas van de Kamp; Elias Hamann; Marcus Zuber; et al. (Proceedings of the National Academy of Sciences, 2025)
Olfaction is a critical sense for tetrapods, playing a key role in survival and reproduction by aiding in food detection, predator avoidance, and social interactions. Olfactory performance has been experimentally tested in only a few taxa, so comparative analyses rely on anatomical and genomic proxies. Among anatomical proxies, the olfactory bulb endocast is widely used, particularly in extinct species, where it is often the only preserved proxy and can be reconstructed even in million-year-old fossils. While the functional significance of chemoreceptor genes has received attention, the extent to which the olfactory bulb endocast correlates with genomic proxies remains unclear. Using brain endocasts across all mammalian orders, we investigated the relationship between the absolute (absOB) and relative (relatOB) volumes of the olfactory bulb endocast and the number of intact chemoreceptor genes. While no clear correlations were found between absOB and the genomic proxies tested, we identified a significant correlation between relatOB and the total number of combined intact chemoreceptor genes (CombChemo), primarily driven by olfactory receptor genes (OR). Leveraging this correlation, and aiming to infer olfactory capabilities in taxa for which only the skull is available, we estimated OR numbers for three mammalian orders lacking genomic data, as well as for five extinct mammals. Building on studies that have established a link between intact OR and olfactory sensitivity and discrimination, we conclude that relatOB enables inference of olfactory capabilities in mammals. This provides a basis to investigate sensory evolution and opens perspectives for interpreting paleoecology and behavior of extinct mammals.